2013
DOI: 10.1089/ten.tec.2011.0473
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-Based Tissue Engineering: Comparison of Different Methods of Autologous Fibrinogen Isolation

Abstract: The results of the present study demonstrated that ethanol precipitation is a simple and effective method for isolation of fibrinogen and a suitable alternative to cryoprecipitation. This technique allows minimization of the necessary blood volume for fibrinogen isolation, particularly important for pediatric applications, and also has no negative influence on microstructure, mechanical properties, cell proliferation, or tissue development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…Isolation techniques (eg, cryoprecipitation and ethanol precipitation), batch to batch variability, and composition (eg, concentration of thrombin, fibrinogen, factor XIII, and antifibrolytics) lead to different mechanical and biological properties of the generated clots. 16,17 For example, Dickneite et al showed clear differences in hemostatic and clot strength properties of 12 commercially available fibrin sealants. 17 Furthermore, differences in component origin may change the biochemistry of the clot, like interspecies or pooled and single donor.…”
Section: Difficulties Involved In Assessing the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Isolation techniques (eg, cryoprecipitation and ethanol precipitation), batch to batch variability, and composition (eg, concentration of thrombin, fibrinogen, factor XIII, and antifibrolytics) lead to different mechanical and biological properties of the generated clots. 16,17 For example, Dickneite et al showed clear differences in hemostatic and clot strength properties of 12 commercially available fibrin sealants. 17 Furthermore, differences in component origin may change the biochemistry of the clot, like interspecies or pooled and single donor.…”
Section: Difficulties Involved In Assessing the Literaturementioning
confidence: 99%
“…These include cryoprecipitation or chemical precipitation with ethanol, ammonium sulfate, or poly(ethylene glycol). 16,90 The principal advantage of cryoprecipitation over other procedures is that no potentially cytotoxic chemicals are required for this process; however, it is time-consuming and the fibrinogen yield is extremely low. Cryoprecipitation is time-consuming but chemical precipitation is rapid.…”
Section: Fibrin Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The test was performed according to a standard protocol described elsewhere. 18 Briefly, HFFs or HUVECs were cultured in a 96-well plate at a density of 1 · 10 4 cells/well in standard medium (DMEM and 10% FBS for HFFs; EGM-2 for HUVECs). After 48 h of preculturing, medium was replaced with test medium (appropriate medium without FBS, preincubated with nonfunctionalized and biofunctionalized PLLA for 72 h at 37°C).…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…Fibrin is an attractive scaffold material because of its autologous origin, rapid polymerization, the tunable degradation using protease inhibitors, 20 the autologous release of growth factors, 21 and the manufacturability into complex three-dimensional (3D) geometries with homogeneous cell seeding. 22 However, being a hydrogel, fibrin is mechanically weak and TEHVs based on fibrin could only be implanted in the low-pressure pulmonary circulation of animal models.…”
Section: Introductionmentioning
confidence: 99%